Involvement of Two Paralogous Methoprene-Tolerant Genes in the Regulation of Vitellogenin and Vitellogenin Receptor Expression in the Rice Stem Borer, Chilo suppressalis - Miao, Lijun; Zhang, Nan; Jiang, Heng; Dong, Fan; Yang, Xuemei; Xu, Xin; Qian, Kun; Meng, Xiangkun; Wang, Jianjun (Frontiers in Genetics, 2020)
Besides the function of preventing metamorphosis in insects, the juvenile hormone (JH) plays a role in female reproduction; however, the underlying mechanism is largely unknown. The methoprene-tolerant (Met) protein belongs to a family of basic helix-loop-helix–Per-Arnt-Sim (bHLH-PAS) transcription factors and functions as the JH intracellular receptor. In this study, two full length cDNAs encoding Met (CsMet1 and CsMet2) were isolated from the rice stem borer, Chilo suppressalis. Structural analysis revealed that both CsMet1 and CsMet2 exhibited typical bHLH, PAS-A, PAS-B, and PAC (PAS C terminal motif) domains. Comparative analysis of transcript level using reverse transcription-quantitative PCR (RT-qPCR) revealed that CsMet1 was predominant in almost all examined developmental stages and tissues. Treatment with methoprene in vivo induces the transcription of both CsMet1 and CsMet2. Notably, injection of dsCsMet1 and dsCsMet2 suppressed the expression levels of vitellogenin (CsVg) and Vg receptor (CsVgR). These findings revealed the potential JH signaling mechanism regulating C. suppressalis reproduction, and provided evidence that RNAi-mediated knockdown of Met holds great potential as a control strategy of C. suppressalis.